(untitled) (Quinto Sol, 2016)
By proposing as a subject of analysis the interconnection between immigration and health in a leading nation of the arrival (and departure) of thousands and thousands of people, we wanted to accentuate one of the key and little explored problems so far. Given that immigration and health are global phenomena and, at the same time, local, the call for this dialogue included different specialists, both Argentine and foreign, whose advances penetrate aspects at different levels and contexts. Comparison, an exercise used and abused by the profession, is an important tool to single out and encompass both the national “case” in contrast to countries with an immigration matrix and, in turn, apply it in regions whose structure depended on the overseas population. The historiography of health and disease undoubtedly provides a significant basis for the interpretation of demographic indices of analysis -natality, mortality, morbidity, fertility ... - as well as their modification over time. Of course, one of the greatest technical-scientific transformations of the 19th century, with a direct consequence on the lengthening of the life expectancy of the population, was the revolution in microbiology. Both bacterological research and its specific technical-professional implications had an enormous impact on human life - without being exhaustive, two examples such as the medicalization of childbirth, universal vaccination serve to visualize this process - and paved the way for the configuration from a field of experts and its closer link with the formation of public bodies, as well as a greater private concern for the health of individuals and families. Immigration, like health, is not an easy phenomenon to tackle. Consequently, it is not possible to do it from a univocal look either. Both propose a necessary investigation of the global context, but at the same time it is feasible and desirable to return to the particular “case” -localities, areas of circulation-, and even, to the stories and narratives of immigrants. For readers specializing in historiography of health and disease, as well as experts in the history of immigration, these stories will undoubtedly be essential. But they are also so for those who are on the fringes of both problems and want to find lines of reflection on the new contributions of the (broad, indefinable in its margins and at the same time exciting), new social history.